Hypertonicity counteracts MCL‐1 and renders BCL‐XL a synthetic lethal target in head and neck cancer. (2nd August 2020) - Heimer, Sina; Knoll, Gertrud; Neubert, Patrick; Hammer, Karin P.; Wagner, Stefan; Bauer, Richard J.; Jantsch, Jonathan; Ehrenschwender, Martin
Abstract : Head and neck squamous cell carcinoma (HNSCC) is an aggressive and difficult‐to‐treat cancer entity. Current therapies ultimately aim to activate the mitochondria‐controlled (intrinsic) apoptosis pathway, but complex alterations in intracellular signaling cascades and the extracellular microenvironment hamper treatment response. On the one hand, proteins of the BCL‐2 family set the threshold for cell death induction and prevent accidental cellular suicide. On the other hand, controlling a cell's readiness to die also determines whether malignant cells are sensitive or resistant to anticancer treatments. Here, we show that HNSCC cells upregulate the proapoptotic BH3‐only protein NOXA in response to hyperosmotic stress. Induction of NOXA is sufficient to counteract the antiapoptotic properties of MCL‐1 and switches HNSCC cells from dual BCL‐XL/MCL‐1 protection to exclusive BCL‐XL addiction. Hypertonicity‐induced functional loss of MCL‐1 renders BCL‐XL a synthetically lethal target in HNSCC, and inhibition of BCL‐XL efficiently kills HNSCC cells that poorly respond to conventional therapies. We identify hypertonicity‐induced upregulation of NOXA as link between osmotic pressure in the tumor environment and mitochondrial priming, which could perspectively be exploited to boost efficacy of anticancer drugs. Abstract : Apoptosis resistance is a hallmark of cancer. In head and neck squamous cell carcinoma (HNSCC), the cooperative interplay between BCL‐XL and MCL‐1 grants apoptosis protection and drives treatment failure. Here, we show that hyperosmotic stress in the tumor environment shrinks dual BCL‐XL/MCL‐1 protection to exclusive BCL‐XL addiction. Hyperosmotic stress counteracts the antiapoptotic function of MCL‐1, heightens death priming, and renders BCL‐XL a synthetically lethal therapeutic target in HNSCC.